1994
DOI: 10.1021/bi00203a037
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of in vitro nucleic acid strand annealing activity of heterogeneous nuclear ribonucleoprotein protein A1 by reversible phosphorylation

Abstract: Phosphorylation in vivo of several proteins in the mammalian heterogeneous nuclear ribonucleoprotein complex (hnRNP), including A1, has been observed and proposed as a regulatory step in pre-mRNA splicing [Maryland, S. H., Dwen, P., & Pederson, T. (1993) Proc. Natl. Acad. Sci. U.S.A. 90, 7764-7768]. We examined the ability of recombinant hnRNP protein A1 to act as a substrate for a number of purified Ser/Thr protein kinases in vitro. A survey of seven protein kinases showed that A1 was heavily phosphorylated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…However, it is also possible that such Ca 2ϩ -binding factors may directly or indirectly regulate IRES activity in response to changes in cytosolic Ca 2ϩ levels. Indeed, the IRES-trans acting factors (ITAFs) hnRNP A and hnRNP C are known to bind calmodulin in the presence of Ca 2ϩ (44) and in addition, hnRNP A is also known to be regulated by PKC phosphorylation which alters its ability to bind RNA (45,46). Thus, these data potentially link Ca 2ϩ signaling pathways to ITAF activity.…”
Section: Discussionmentioning
confidence: 98%
“…However, it is also possible that such Ca 2ϩ -binding factors may directly or indirectly regulate IRES activity in response to changes in cytosolic Ca 2ϩ levels. Indeed, the IRES-trans acting factors (ITAFs) hnRNP A and hnRNP C are known to bind calmodulin in the presence of Ca 2ϩ (44) and in addition, hnRNP A is also known to be regulated by PKC phosphorylation which alters its ability to bind RNA (45,46). Thus, these data potentially link Ca 2ϩ signaling pathways to ITAF activity.…”
Section: Discussionmentioning
confidence: 98%
“…HnRNP proteins are also regulated by phosphorylation (8,21,29). Phosphorylation of LR1 is required for binding to DNA target sequences, but the kinase that mediates LR1 phosphorylation is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although stimulation of these signalling pathways markedly increased reporter gene expression in cells expressing GAL4-hnRNP D0 (Table 1), stimulation increased reporter gene expression of control samples as well. Protein kinase C, protein kinase A and casein kinase II phosphorylate hnRNP A1 in itro, and it has been shown that its phosphorylation state affects its ability to interact with RNA [34,35]. hnRNP A2 is also phosphorylated by casein kinase II [36].…”
Section: Discussionmentioning
confidence: 99%